Long-term outcomes of three distinct once-daily schedules for accelerated partial breast irradiation - Lorenzo Vinante; Michele Avanzo; Angela Caroli; Carlo Furlan; Andrea Sacilotto; Lorena Baboci; Tiziana Perin; Martina Urbani; Alessandro Favero; Simon Spazzapan; Fabio Puglisi; Maurizio Mascarin; et al. (Breast)
Background and purpose: To date, accelerated partial breast irradiation (APBI) regimens are highly heterogeneous. Twice-daily schedules show comparable local control to whole-breast radiotherapy but with worse toxicity and cosmesis profiles. Conversely, once-daily regimens are better tolerated, though dose and number of fractions are yet not standardized. Therefore, the aim of this study was to evaluate the efficacy and tolerability of three different once-daily APBI schedules. Materials and methods: Three consecutive phase-2 trials were conducted at a single national cancer center to assess three once-daily APBI schedules (40Gy in 10 fractions, 35Gy in 7 fractions, and 28Gy in 4 fractions) delivered with 3D-conformal radiotherapy. All patients were at least 60 years old and had early-stage breast cancer (pT1-2,pN0-N1mic). Toxicity and cosmesis were evaluated by physicians using the CTCAE 4.0 scale and the Harvard score, respectively. Recurrence rates and survival outcomes at 5 and 10 years were estimated using the Kaplan-Meier method. Results: A total of 189 patients were enrolled, with a median follow-up of 10.2 years. Patients treated with 40Gy in 10 fractions, 35Gy in 7 fractions and 28Gy in 4 fractions were 80 (42%), 73 (39%), and 36 (19%), respectively. Acute toxicity was low and comparable across schedules, whereas grade≥2 late toxicity and poor cosmesis were significantly worse with the shorter schedule. The 10-year estimated in-breast tumour recurrence rate was 5.5%, comparable to the limited literature reporting long-term outcomes. Conclusions: Once-daily APBI delivered with 3D-conformal radiotherapy was effective; however, regimens with fewer than 5 fractions may be associated with increased toxicity and worse cosmesis.